“Corporate Scene Investigation”: A Praxeological Attempt to Sketch the Profile of the Entrepreneur in Modern Business - Octavian-Dragomir Jora; Mihai-Vladimir Topan; Radu Cristian Muşetescu; Matei-Alexandru Apăvăloaei (Amfiteatru Economic)
Mature capitalism and market economy realities become intelligible also by scrutinizing their “prodigal children”: modern business corporations. But these are not some undivided entities. Beyond the place in the global division of labour, they are fiefs of in-built specialization among the corporate governance stakeholders, each of them representing individual-based aggregations of pure catallactic functions. With an atomized, anonymous, asymmetrical and amalgamated ownership in a globalized capital market, with the multi-level directorship, delegated to harmonize profit-orientated investment interests, with creditors, but also with other suppliers of factors of production, modern corporations seem to have overshadowed both the real entrepreneurs-actors as well as the pure corresponding function. Our article is a (praxeo)logical exercise to pinpoint and reveal the realistic field of definition of the “entrepreneurship function” within the modern corporate spectrum, delimiting and portraying the entrepreneurial aspect out of the real characters that inhabit the corporate entourage (precisely said, of shareholders, managers, creditors). It seems that the modern literature on the law and economics of the firm has lost sight of the entrepreneur(ship), whose presence is felt but rarely positively identified. The endeavour to locate and isolate this, along with the associated incentives and logic of action is a task with some analytical merits. A thorough discrimination of the entrepreneurs’ position inside the corporate field and, respectively, of the “natural” vs. “allowed” decision spheres can generate sounder judgments about the wellstructured and poorly-structured companies (good vs. poor corporate governance) or about institutions found to be business (un)friendly (good vs. poor corporate law-making). We define “good governance” at the level of the corporate form the situation when incentives are aligned with rights and obligations, and the “good law” the norm which does not alter the common sense of property rights and freedom of contracting. Without knowing them, any legal organization of the corporate form will be fraught with problems.